TRADITIONAL MADRASAH, STATE POLICIES AND THE RISE OF INTEGRATED ISLAMIC SCHOOLS IN JAMBI (State Islamic University (UIN) of Sunan Ampel Surabaya, 2021)
This paper discusses why the schools were well-liked and flourished; what factors drive this phenomenon? Different from many studies that have analyzed the development of integrated Islamic schools in general in Indonesia, this article focuses on the more specific Jambi case. Using social movement theory, this article argues that in addition to liberal policies that open wide opportunities for anyone to express themselves in the public sphere, including Islamists, the need for the Jambi Malay community for religious education is also an important factor. While previously this need was fulfilled by the presence of traditional Malay madrasas, which teach Islam in the afternoon after students return from school, the education standardization policy implemented by the Indonesian government has made their existence deteriorate. Taking advantage of these conditions, integrated Islamic schools have emerged to offer a full-day Islamic education model to the Muslim middle class, who are anxious about their children’s future due to lack of supervision after their time is up for work.